Cationic high-solid-content acrylic resin and preparation method thereof as well as marine antifouling paint and preparation method thereof

By developing cationic high-solid content acrylic resin, combining hydroxy cations and dendritic polyester polyols, to form a dense network structure, it solves the environmental pollution problem of traditional marine antifouling coatings and achieves efficient marine microbial protection and coating performance improvement.

CN119661797AActive Publication Date: 2025-03-21THE NAVAL MEDICAL UNIV OF PLA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510186114.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-03-21
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

Traditional marine antifouling coatings contain harmful substances, and environmentally friendly coatings require a higher proportion of organic solvents, resulting in a greater environmental impact. Acrylic resins cannot effectively resist the erosion of the extreme marine environment when used alone.

Method used

A cationic high-solid content acrylic resin was developed to form a dense three-dimensional network structure by introducing hydroxyl cationic groups and dendritic polyester polyols, combining aliphatic polyurethane as a curing agent to improve the antibacterial, weathering and mechanical properties of the coating.

Benefits of technology

It significantly improves the adhesion, durability and corrosion resistance of the coating, can effectively prevent the adhesion and erosion of marine microorganisms, extend the service life of the coating, and reduce maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661797A_ABST
    Figure CN119661797A_ABST
Patent Text Reader

Abstract

The invention provides cationic high-solid-content acrylic resin and a preparation method thereof as well as a marine antifouling paint and a preparation method thereof. The preparation method comprises the following steps: firstly, synthesizing cationic high-solid-content acrylic resin with hydroxyl, and introducing a cationic group with an antibacterial effect into a polymer network through quaternization of dimethylaminoethyl acrylate; and the dendritic polyester polyol is added to increase the three-dimensional network density of the polymer, so that the coating is endowed with excellent mechanical properties and corrosion resistance. Finally, an aliphatic polyurethane oligomer is used as a curing agent, and after curing, the marine antifouling coating which is antibacterial, low in surface energy and excellent in weather resistance is obtained. The coating has a remarkable effect of preventing adhesion of marine microorganisms, is particularly suitable for protecting the surfaces of offshore platforms, ships and large marine equipment, is more environment-friendly, and conforms to national energy-saving and carbon-reducing strategic requirements and marine protection concepts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of marine antifouling coatings, and in particular relates to a cationic high-solid content acrylic resin and a preparation method thereof, and also relates to a marine antifouling coating comprising the cationic high-solid content acrylic resin and a preparation method thereof. Background Art

[0002] In addition to dealing with complex climate environments, offshore equipment also has to withstand corrosion from marine microorganisms. The adhesion and proliferation of microorganisms will accelerate the corrosion of offshore platforms, ports and submarine pipelines. Not only that, when microorganisms adhere to the surface of ships, it will increase navigation energy consumption, which is not in line with the carbon emission reduction strategy. As my country's marine strategic position continues to improve, higher requirements are also placed on the protection of offshore equipment. Traditional marine antifouling coatings have been banned because they contain harmful substances such as organic tin, which cause great harm to the marine environment. Most of the newly developed environmentally friendly marine antifouling coatings also require a considerable proportion of organic solvents to be used in conjunction, which still has a huge impact on the environment.

[0003] In order to solve this problem, high-solid content coatings came into being. They have a high solid content, usually more than 50%, so the emission of volatile organic compounds, or VOCs, is very low. At the same time, they have a low viscosity, are easy to flow and apply, and can obtain a smooth coating, improving the hiding power, adhesion and durability of the coating. In marine antifouling coatings, the application of this resin can significantly improve the adhesion and durability of the coating. In addition, due to the corrosiveness and biological attachment problems in the marine environment, high-solid content resins can form a stronger protective layer to resist seawater erosion and the attachment of marine organisms, thereby extending the service life of the coating and reducing maintenance costs.

[0004] Acrylic resin has strong adhesion and UV resistance, as well as the characteristics of abrasion resistance, corrosion resistance and algae resistance. It has a wide range of applications and is an important raw material for the preparation of marine antifouling coatings, especially for offshore drilling platforms and marine engineering structures. However, it mainly plays a role in film formation and controlling the release of antifouling agents in the coating. When used alone as a marine coating, it has no ability to kill microorganisms and has no direct contribution to the antifouling effect of the coating. At the same time, due to the short molecular chain of acrylic acid, the polymer network of the coating formed is not dense and cannot resist the erosion of the extreme marine environment. Summary of the invention

[0005] The present invention is directed to the above problems and provides a cationic high-solid content acrylic resin and a preparation method thereof, and a marine antifouling coating containing the same and a preparation method thereof.

[0006] The invention aims at the shortcomings of high-solid-content acrylic resin in the preparation of marine antifouling coatings. The present invention first synthesizes a cationic high-solid-content acrylic resin with hydroxyl groups, and introduces cationic groups with antibacterial effects into the polymer network through quaternization of dimethylaminoethyl acrylate. Then, dendritic polyester polyols are added to increase the three-dimensional network density of the polymer, thereby giving the coating excellent mechanical properties and anticorrosive properties. Finally, aliphatic polyurethane oligomers are used as curing agents, and after curing, a marine antifouling coating with antibacterial, low surface energy and excellent weather resistance is obtained. The coating has a significant effect on preventing the adhesion of marine microorganisms, and is particularly suitable for protecting the surfaces of offshore platforms, ships and large marine equipment.

[0007] Cations can interact with the negatively charged phospholipid molecules on the bacterial cell membrane. Positive charges can destroy the integrity of the cell membrane, increase membrane permeability, and cause cell membrane rupture or instability, leading to leakage of intracellular substances and ultimately bacterial death. The hydroxyl groups on the dendritic polyester polyols and the hydroxyl groups provided by hydroxyethyl acrylate react with the isocyanate groups of the aliphatic polyurethane to form a dense three-dimensional network structure, greatly enhancing the corrosion resistance and weather resistance of the coating. At the same time, the highly branched structure of the dendritic polyester polyols provides excellent cross-linking ability and stronger coating hardness, thereby improving the wear resistance and scratch resistance of the coating. In addition, their branched structure can significantly improve the flexibility and adhesion of the coating, reducing the possibility of cracking during use.

[0008] Based on the above research, the technical solution to be protected by the present invention is as follows:

[0009] In a first aspect, the present invention provides a cationic high-solid acrylic resin, which is a high-solid low-viscosity acrylic resin with a solid content of 70%, a molecular weight of 65000-70000 (Mw), and a hydroxyl value of 5-6 mg KOH / g.

[0010] In terms of composition, the high-solid low-viscosity acrylic resin comprises 15-20 parts of component A and 12-15 parts of component B, based on weight parts.

[0011] The component A includes acrylic monomer, antibacterial monomer, initiator, chain transfer agent, solvent, antioxidant and ethyl bromide additive.

[0012] Component B includes solvent propylene glycol dimethyl ether acetate, dendritic polyester polyol, and aliphatic polyurethane curing agent.

[0013] Preferably, in component A, the acrylic monomers include 100-120 parts by weight of methyl methacrylate, 30-35 parts of 2-ethylhexyl acrylate, 10-12 parts of hydroxyethyl acrylate, and 55-60 parts of bornyl acrylate.

[0014] The antibacterial monomer is selected from dimethylaminoethyl acrylate. The cation comes from the tertiary amine group of quaternized dimethylaminoethyl acrylate. The cationic amino structure can interact with the anionic components on the bacterial cell membrane, destroying the integrity of the cell membrane, causing cell matrix leakage, thereby inhibiting or killing bacteria. Among them, the amount of dimethylaminoethyl acrylate is 5%-15% of the total amount of acrylic acid monomers.

[0015] Bornyl acrylate is selected from isobornyl acrylate, and can also be replaced by one of the acrylates containing a ring structure such as bornyl methacrylate or cyclohexyl acrylate, so as to increase the molecular weight of the synthetic acrylic resin and reduce the viscosity of the synthetic resin.

[0016] The initiator is AIBN, and the overall proportion is controlled between 0.5% and 1.5% of the acrylic acid monomer; the chain transfer agent is tert-dodecyl mercaptan or n-dodecyl mercaptan, and the addition amount of tert-dodecyl mercaptan is 1% to 2% of the acrylic acid monomer, and the addition amount of n-dodecyl mercaptan is 1.5% to 3% of the acrylic acid monomer.

[0017] The weight proportions of the solvent propylene glycol methyl ether acetate are 60-80 parts, ethyl bromide is 4-6 parts, and the antioxidant is 1-2 parts.

[0018] The antioxidant is selected from the prior art, such as hydroxyphosphonate, hydroxymethylpropylphenyl ether and the like.

[0019] In component B, the polyester polyol is a dendritic polyester polyol H40p, with a hydroxyl value of 500 mg KOH / g, and is dissolved in propylene glycol dimethyl ether acetate. The amount added is low between 0.5% and 2%, medium between 2% and 5%, and high above 5% relative to the total amount of acrylic monomers. When used as an additive to increase the crosslinking degree of coatings, it is generally added in a medium range, that is, between 2% and 5%, to increase the density of the crosslinking system, which can give the coating high durability, wear resistance, adhesion and weather resistance.

[0020] The polyurethane curing agent is an aliphatic polyurethane curing agent HDI, with a viscosity of 2500 mpa·s at 25°C and a -NCO content of 21.8±0.3%. When used with acrylic resin and polyester polyol, the ratio of -NCO to -OH is controlled between 1.2:1-1.4:1. The acrylate-polyester polyol-polyurethane coating formed within this range has excellent stain resistance, UV resistance, mechanical properties and chemical corrosion resistance, and can adapt to complex and harsh marine atmospheric environments.

[0021] More preferably, the cationic high solid content acrylic resin provided by the present invention comprises the following components: in parts by weight: (1) 15-20 parts of component A; and (2) 12-15 parts of component B.

[0022] Component A comprises, by weight: 100-120 parts of methyl methacrylate, 30-35 parts of 2-ethylhexyl acrylate, 10-12 parts of hydroxyethyl acrylate, 55-60 parts of isobornyl acrylate, 10-12 parts of dimethylaminoethyl acrylate, 60-80 parts of propylene glycol methyl ether acetate, 1-3 parts of AIBN, 3-6 parts of tert-dodecyl mercaptan, 4-6 parts of ethyl bromide, and 1-2 parts of antioxidant.

[0023] Component B comprises, by weight, 12-13 parts of propylene glycol dimethyl ether acetate, 0.1-0.3 parts of dendritic polyester polyol, and 2-4 parts of aliphatic polyurethane curing agent.

[0024] In a second aspect, the present invention provides a method for preparing the above-mentioned cationic high solid content acrylic resin, comprising the following steps:

[0025] A. Preparation of cationic high solid content acrylic acid solution

[0026] (1) Weigh the solvent propylene glycol methyl ether acetate and add it into a container. Stir at 300-320 r / min and heat to 72 ± 1°C. Condensate and reflux.

[0027] (2) Weigh the preset proportion of acrylic monomer, antibacterial monomer, initiator, chain transfer agent and antioxidant, stir evenly and then drop them into the reaction container at a uniform speed; specifically, weigh the monomers methyl methacrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate, isobornyl acrylate and dimethylaminoethyl acrylate, mix evenly and then add initiator AIBN, chain transfer agent dodecanethiol and antioxidant. Since most substances are liquid, the mixture is also in liquid state after mixing. Transfer the mixture to a constant pressure funnel and drop it into a three-necked flask at a uniform speed of 0.3-0.4 ml / min.

[0028] After the addition is completed, the system temperature is raised to 75°C, the reaction is continued overnight, and then the temperature is raised to 80°C for reaction for 2 hours. When the polymerization reaction is completed, the temperature is lowered to 60°C, ethyl bromide is added and the reaction is continued for another 2 hours, and the temperature is lowered to 40°C to obtain the product.

[0029] B. Preparation of cationic high solid content acrylic resin

[0030] Dissolve the dendritic polyester polyol in propylene glycol dimethyl ether acetate to obtain a transparent resin solution, then add it to the acrylic acid solution and stir for 5-10 minutes until it is uniform; weigh the polyurethane curing agent according to the molar ratio of isocyanate group to hydroxyl group of 1.2:1 and add it to the solution. Stir for about 5-10 minutes and let it stand to remove bubbles.

[0031] In the present invention, the acrylic monomers all contain a stabilizer, 4-methoxyphenol MEHQ, which is removed by alkaline alumina before use.

[0032] The third aspect of the present invention provides the use of the above-mentioned cationic high-solid content acrylic resin in the preparation of marine antifouling coatings.

[0033] In a fourth aspect, the present invention provides a marine antifouling coating, comprising a cationic high solid content acrylic resin, pigments, fillers and additives, wherein the cationic high solid content acrylic resin is as described in any one of the above items.

[0034] The pigment and filler are selected from one of silicon dioxide, ferric oxide, silicon dioxide, zinc oxide, clay, barium sulfate and mica powder; the auxiliary agent is one or more of a leveling agent, a defoaming agent and a dispersant.

[0035] Specifically, the leveling agent is one of BYK-S3700, BYK-354, DH-3187, and FLOW-100; the defoamer is one of CL-266, KS-66, and KSZ-108; and the dispersant is one of S-100 polyether polymer dispersant, EFKA-4401, and 6161A. In actual operation, you can choose from them according to actual needs.

[0036] In a fifth aspect, the present invention provides a method for preparing the above-mentioned marine antifouling coating, comprising the following steps:

[0037] The obtained cationic high-solid content acrylic resin is added to a dispersing device, and an auxiliary agent is added. The rotation speed is controlled at 100 to 200 rpm and dispersed for about 30 minutes. Then, pigments and fillers are added and dispersed at 500 to 800 rpm for about 30 minutes to obtain an antifouling coating.

[0038] The antifouling coating is applied to the surface of the substrate, and the antifouling coating with a film thickness of 100 to 200 μm is prepared through cross-linking and curing. When operating in the laboratory, in order to save time, after brushing, the substrate is left to stand for 2 hours until the coating solvent partially evaporates, and then transferred to an oven, the oven temperature is set to 100°C, and the heating curing time is 2 hours. After the curing reaction is completed, the substrate is left to stand at room temperature for 2 hours until it is completely cooled, and then the next performance test is carried out.

[0039] Compared with the existing method, the present invention has the following advantages:

[0040] The present invention obtains cationic high-solid content acrylic resin as the main part of the marine antifouling coating by free radical polymerization. The ultra-high solid content of more than 70% means ultra-low VOC emissions, which is more environmentally friendly and meets the national energy conservation and carbon reduction strategic needs and marine protection concepts.

[0041] Since the molecular chain of high-solid low-viscosity resin is short, it is difficult to form a stable cross-linked dense network structure. The coating performance obtained when used alone is general. The present invention increases the cross-linking density by introducing branched polyester polyols, and uses aliphatic polyurethane as a curing agent. The branched polyester polyol provides multiple binding sites between the isocyanate group and the acrylic acid molecular chain, which can form a three-dimensional cross-linked network. The formed coating has excellent mechanical properties, better flexibility, better adhesion, and is more tightly combined with the substrate. The use of aliphatic polyurethane and polyester polyol can improve the UV resistance, temperature and humidity resistance of the coating, making the coating more suitable for marine environments.

[0042] The advantages of cationic antimicrobial ingredients are broad-spectrum antibacterial properties, which are effective against a variety of bacteria, fungi and algae, and have a broad-spectrum antibacterial effect; they also have low toxicity. Compared with some traditional antimicrobial agents, this compound is generally less toxic and more friendly to the human body and the environment. More importantly, when cations are used as the main sterilization ingredients, they are not easy to develop drug resistance and can effectively hinder the attachment of marine microorganisms for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The comparison of the antibacterial and antifouling test results of the blank control group and Example 1 is shown;

[0044] Figure 2 The blank control group and the algae attachment experiment results of Example 1 are shown. DETAILED DESCRIPTION

[0045] The following examples and experimental examples are provided to further illustrate the present invention and should not be construed as limiting the present invention. The examples do not include a detailed description of conventional methods, which are well known to those skilled in the art and are described in many publications.

[0046] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the present invention, and the preferred implementation methods and materials described in the specific embodiments are for demonstration purposes only.

[0047] The present invention uses a hydroxyl-containing cationic acrylic resin as the main body, and the hydroxyl groups on the acrylic resin molecular chain react with the dendritic polyester polyols and the isocyanate groups together to finally form an antibacterial and antifouling coating with low surface energy and excellent weather resistance. Specifically, the main part is obtained by adjusting the ratio of methyl methacrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate, dimethylaminoethyl acrylate, initiator AIBN and chain transfer agent tert-dodecyl mercaptan to obtain a cationic high-solid acrylic resin. The quaternary ammonium salt of dimethylaminoethyl acrylate is used to introduce cations with antibacterial effects into the polymer network, the dendritic polyester polyols are used as additives to increase the density of the cross-linking system and enhance the mechanical properties, and the aliphatic polyurethane is used as a curing agent to improve the antifouling, corrosion resistance and weather resistance of the coating. Finally, after blending with pigments and fillers, a marine antifouling coating with excellent comprehensive performance is obtained.

[0048] 1. Preparation of cationic high solid content acrylic resin coating

[0049] Example 1

[0050] A. Preparation of cationic high solid content acrylic resin solution

[0051] Weigh 26.2 g of propylene glycol dimethyl ether acetate and add it to a three-necked flask, turn on the condensation reflux device, and after cooling, raise the temperature of the oil bath to 72 °C. At this time, the stirring speed is controlled at 300 r / min. Weigh 35 g of methacrylate, 10.4 g of 2-ethylhexyl acrylate, 17.6 g of isobornyl acrylate, 3.5 g of hydroxyethyl acrylate, and 3.5 g of dimethylaminoethyl acrylate and add them to a beaker. Stir on a magnetic stirrer for 3 minutes to mix. Weigh 0.56 g of AIBN, 1.05 g of tert-dodecyl mercaptan and 0.35 g of antioxidant and add them to a beaker. Pour all monomers, initiators and chain transfer agents into a constant pressure funnel and add them dropwise to the reactor at a uniform rate of 0.3-0.4 ml / min. After the addition was completed, the temperature of the oil bath was raised to 75 °C overnight, 0.05 g AIBN dissolved in 1 g propylene glycol dimethyl ether acetate was added, the temperature was raised to 80 °C for reaction for 2 hours, the temperature was lowered to 60 °C, 3.2 g ethyl bromide was added for further reaction for 2 hours, the temperature was lowered to 40 °C for discharge, and the reaction was completed to obtain a cationic high solid content acrylic resin solution.

[0052] B. Preparation of cationic high solid content acrylic resin cured coating

[0053] Take 0.07 g of dendritic polyester polyol and dissolve it in 3.75 g of propylene glycol dimethyl ether acetate, heat it to 50 °C, and stir it for 10 minutes until it is completely dissolved to obtain a transparent resin solution. Pour the solution into the acrylic acid solution in step A and stir it for another 5 minutes to disperse it evenly. Weigh the polyurethane curing agent according to 1.2-1.4 times the molar mass of the hydroxyl group, that is, 0.875 g N3300, add it to the system, and stir it at room temperature for 5-10 minutes until it is completely mixed.

[0054] Take 0.5 g of the solution and brush it evenly on the pretreated tinplate or glass slide. Let it stand for 2 hours until the coating solvent evaporates. When the coating solution cannot flow obviously, transfer it to the oven. Set the oven temperature to 100 °C and heat curing time for 1-2 hours.

[0055] Example 2

[0056] The only difference from Example 1 is that the content of the cationic monomer dimethylaminoethyl acrylate is 10% of the acrylic acid monomer, and the specific mass is 7 g.

[0057] The specific processes of Examples 1 and 2 are the same, but the ratios of additives and cationic monomers are different. The specific details are shown in Table 1 below:

[0058] Table 1 Summary of formulation compositions of Examples 1 to 2

[0059]

[0060] 2. Technical Effect Verification

[0061] The cationic high-solid acrylic coating prepared in the above embodiment was tested by using a cross-hatch tape peeling adhesion test, a surface energy test, an antibacterial test, and an algae adhesion test.

[0062] Test 1: Adhesion test---frame tape peeling test

[0063] A 25 mm×75 mm×1 mm glass slide was pretreated, cleaned and dried, and then coated with the cationic high solid content acrylic resin coating synthesized in Examples 1-2, baked at 100° C. for 1 hour, and then allowed to stand in a dry environment for 2 hours for use.

[0064] Use a grid drawer to draw a pattern with a spacing of 1mm×1mm on the coating, quickly stick the tape on the scratch, press until it is fully in contact, then tear off the tape, observe the coating damage, and grade the coating adhesion. The standards are as follows:

[0065] Grade 0B: The peeling area of ​​paint is greater than 65%; Grade 1B: The peeling area is greater than 35% and less than 65%; Grade 2B: The peeling area is more than 15% and less than 35%; Grade 3B: The peeling area is greater than 5% and less than 15%; Grade 4B: The actual damage in the grid area is less than or equal to 5%; Grade 5B: There is no peeling on the edge of the grid and the cut edge is completely smooth. This is the highest level of adhesion.

[0066] Test 2: Surface free energy test

[0067] The contact angles of deionized water and diiodomethane of the coating were measured using a Dataphysics OCA20 contact angle meter, and the surface energy of the coating was calculated according to the WORK model.

[0068]

[0069] There are two unknowns in the equation and To solve this problem, two liquids with known dispersion and polarity components are needed. When testing, two liquids with mainly polar and mainly dispersion components should be selected.

[0070] Test 3: Antibacterial and antifouling test

[0071] The antifouling performance test of the coating refers to the national standard GB / T 21866-2008 "Determination of antibacterial properties and antibacterial effects of antibacterial coatings (paint films)". The coating film is prepared according to the requirements of GB / T1727. The coating is generally applied twice. The second coat is applied after the first coat is dry. The total wet film thickness of the coating is less than 100 μm. The sample should be flat, rust-free, and oil-free. After the plate is painted, it should be dried for 7 days according to the provisions of GB / T9278 before use. The plate size is 50×50 mm. It is sterilized by ultraviolet light on the clean bench for 5 minutes before use.

[0072] Calculation results:

[0073] The formula for calculating the antibacterial rate is: R = (BC / B) × 100%

[0074] Where:

[0075] R——antibacterial rate, expressed as (%), with four significant figures, in accordance with the provisions of GB / T1250;

[0076] B——Average number of recovered bacteria on the blank-proof test plate after 24 hours (CFU / plate);

[0077] C——Average number of bacteria recovered from the antibacterial coating sample after 24 hours (CFU / piece).

[0078] The above three test results are summarized in Table 2 below:

[0079] Table 2 Test results of cationic high solid content acrylic coatings of Examples 1 and 2

[0080]

[0081] The results show that the cured acrylic coating has the highest level of adhesion of 5B, indicating that the resin obtained in the example can adhere well to the substrate without falling off and has excellent adhesion. The surface energy test results show that the surface energy of the cured acrylic coating is low, so it can show effective antifouling performance.

[0082] Figure 1 The pictures of the inhibition results of the antifouling coating on Pseudomonas aeruginosa are shown, and the pictures from left to right are the blank control group and Example 1. The results show that the coating with cations as antibacterial components can have an excellent inhibitory effect on Pseudomonas aeruginosa, indicating the antibacterial effectiveness of marine antifouling acrylic coatings.

[0083] Test 4: Algae adhesion test

[0084] A mixed algae species consisting of green algae, coccoal algae and diatoms was selected and dispersed in an aqueous solution (algae concentration of 20-100 μg / mL), and cultured at room temperature and a relative humidity of 55% to 65%. The sample coated with the resin of Example 1 and the blank control sample were immersed in the algae solution, and the surface algae attachment was recorded regularly. The results are as follows: When the initial algae concentration was 20 μg / mL, no obvious algae attachment was observed on the surface of the resin sample after 168 h, while discrete algae spots had formed on the surface of the blank sample. When the algae solution concentration was increased to 60 μg / mL and immersed for 504 h, the resin surface remained basically clean, while the blank substrate was covered with a dense algae layer and accompanied by the expansion of rust spots. The algae concentration was continued to be increased to 100 μg / mL and the immersion was extended to 576 h. Only sporadic algae spots appeared on the resin surface, while the blank substrate was completely covered with a biofilm formed by algae ( Figure 2 ).

[0085] The unexplained parts involved in the present invention are the same as the prior art or are implemented by the prior art. The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, the equivalent replacement of the raw materials of the product of the present invention, the addition of auxiliary components, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A cationic high solid content acrylic resin, characterized in that: In parts by weight, it comprises 15-20 parts of component A and 12-15 parts of component B; Component A includes acrylic monomer, antibacterial monomer, initiator, chain transfer agent, solvent, antioxidant and ethyl bromide additive; In parts by weight, the acrylic monomer includes 100-120 parts of methyl methacrylate, 30-35 parts of 2-ethylhexyl acrylate, 10-12 parts of hydroxyethyl acrylate, and 55-60 parts of bornyl acrylate; The antibacterial monomer is selected from dimethylaminoethyl acrylate, and the amount used is 5%-15% of the total amount of acrylic acid monomer; The initiator is AIBN, and the overall ratio is controlled to be between 0.5% and 1.5% of the acrylic acid monomer; The chain transfer agent is tert-dodecyl mercaptan or n-dodecyl mercaptan, the addition amount of tert-dodecyl mercaptan is 1%-2% of the acrylic acid monomer, and the addition amount of n-dodecyl mercaptan is 1.5%-3% of the acrylic acid monomer; The solvent is selected from propylene glycol methyl ether acetate, which is 60-80 parts by weight; ethyl bromide is 4-6 parts by weight, and the antioxidant is 1-2 parts by weight. Component B includes solvent propylene glycol dimethyl ether acetate, dendritic polyester polyol and aliphatic polyurethane curing agent. The dendritic polyester polyol is selected from H40p, the hydroxyl value is 500 mg KOH / g, and the added amount is between 0.5% and 5% relative to the total amount of acrylic acid monomers; when used, it is prepared into a solution with propylene glycol dimethyl ether acetate; The aliphatic polyurethane curing agent is selected from HDI, the viscosity at 25°C is 2500 mpa·s, the -NCO content is 21.8±0.3%, and when used with component A and polyester polyol, the ratio of -NCO to -OH is controlled between 1.2:1 and 1.4:

1.

2. The cationic high solid content acrylic resin according to claim 1, characterized in that: In component A, the bornyl acrylate is selected from any one of isobornyl acrylate, bornyl methacrylate and cyclohexyl acrylate.

3. The cationic high solid content acrylic resin according to claim 2, characterized in that: The acrylic resin is a high-solid, low-viscosity acrylic resin with a solid content of 70%, a molecular weight of 65,000-70,000 Mw, and a hydroxyl value of 5-6 mg KOH / g acrylic resin.

4. A method for preparing a cationic high-solid content acrylic resin according to any one of claims 1 to 3, characterized in that: The steps include: A. Preparation of cationic high solid content acrylic acid solution (1) Weigh the solvent propylene glycol methyl ether acetate and add it into a container. Stir and heat it to 72 ± 1 °C, then condense and reflux. (2) Weigh the preset proportions of acrylic monomer, antibacterial monomer, initiator, chain transfer agent and antioxidant. After stirring evenly, uniformly add the mixture dropwise into the reaction container; after the addition is completed, raise the system temperature to 75°C, continue the reaction overnight, then raise the temperature to 80°C and react for 2 hours. When the polymerization reaction is finished, cool the temperature to 60°C, add ethyl bromide and react for another 2 hours, then cool the temperature to 40°C to obtain the product. B. Preparation of cationic high solid content acrylic resin Take the dendritic polyester polyol and dissolve it in propylene glycol dimethyl ether acetate to obtain a transparent resin solution, then add it to the acrylic acid solution and stir for 5-10 minutes until it is uniform; weigh the polyurethane curing agent according to the molar ratio of isocyanate group to hydroxyl group of 1.2:1 and add it to the solution, stir for 5-10 minutes, and let it stand to remove bubbles to obtain the solution.

5. The method for preparing a cationic high solid content acrylic resin according to claim 4, characterized in that: In the step of preparing the cationic high solid content acrylic acid solution of step A, in step (1), the speed of the stirring blade is controlled at 300-320 r / min; in step (2), the solution is added dropwise at a uniform speed of 0.3-0.4 ml / min.

6. Use of the cationic high-solid content acrylic resin according to any one of claims 1 to 3 in the preparation of marine antifouling coatings.

7. A marine antifouling coating, characterized in that: Including cationic high solid content acrylic resin, pigments, fillers and additives, The cationic high solid content acrylic resin is as described in any one of claims 1 to 3; The pigment filler is selected from one of silicon dioxide, ferric oxide, silicon dioxide, zinc oxide, clay, barium sulfate and mica powder; The auxiliary agent is one or more of a leveling agent, a defoaming agent and a dispersant.

8. The marine antifouling paint according to claim 7, characterized in that: The antifouling coating is applied to the surface of a substrate, and is cross-linked and cured to prepare an antifouling coating with a film thickness of 100 to 200 μm.

9. The method for preparing the marine antifouling coating according to claim 7, characterized in that: The method comprises the following steps: adding a cationic high-solid content acrylic resin into a dispersing device, adding an auxiliary agent, and dispersing the mixture at a speed of 100 to 200 rpm for 30 minutes; and then adding a pigment and filler, and dispersing the mixture at a speed of 500 to 800 rpm for 30 minutes to obtain the marine antifouling coating.

Citation Information

Patent Citations

  • Cationic antibacterial polymer and preparation method and application thereof

    CN109705262A

  • Modified third-generation dendritic self-initiation UV resin containing double-type photo-initiation groups

    CN113583201A

  • Hyperbranched polymer molecular structure, preparation method and hyperbranched polymer-based photoresist

    CN114835889A

  • High-solid super-weather-resistant acrylic polyurethane finish paint and preparation method thereof

    CN118389038A

  • Coating agent based on a branched hydroxyl group-containing polyester-modified polyacrylate resin and use thereof

    US6120851A